PSI CHI at PFUR: First Russian Chapter of the International Honor Society in Psychology - Harold Takooshian; I A Novikova; E Yu Chebotareva (Peoples' Friendship University of Russia (RUDN University), 2014)
The publication is devoted to the installation of the first Russian PSI CHI Chapter that took place on 11 October 2013 at Peoples' Friendship University of Russia.